Structural and electrical properties of YBCO added with Nd₂O₃, Gd₂O₃ and Sm₂O₃ nanoparticles - Ramli, Aima (2015)
It is well known that the superconducting properties are strongly dependent on the synthesis technique and processing conditions. Coprecipitation method is frequently used in sample synthesis and thus, chosen in this project due to high homogeneity, low reaction temperature, fine and uniform particle size with non-agglomerate particles, easy set-up and economical, and time saving processing. The Yttrium Barium Copper Oxide (YBCO) samples have been prepared by coprecipitation of metal ion oxalates method added with Nd2O3, Gd2O3 and Sm2O3, x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 wt%. Phase formation and volume fraction of each sample were examined using X-ray diffraction and Rietveld refinement technique. All samples show predominantly Y-123 with non-superconducting phase, Y-211 and impurities, Nd2O3, Gd2O3 and Sm2O3 with orthorhombic structure and Pmmm space group. The volume fractions of nonsuperconducting phase, Y-211 abruptly increase in all systems, might be due to the local differences in the size of Y-211, thus, affect the Tc and Jc in the Y123 system. The microstructure scanning electron microscope (SEM) revealed that the average grain sizes calculated from the Image J, decreased in all systems as the addition of magnetic nanoparticles, Nd2O3, Gd2O3 and Sm2O3 increased indicating that the poor grain connectivity due to the porosities and weak links. The transport measurement of resistance dependence, Tc-onset was measured by using standard four point probe technique. Tc for pure sample is about 92 K. However, Tc decreased to 74 K, 80 K and 88 K for Nd2O3, Gd2O3 and Sm2O3, respectively. The suppression on Tc-onset was attributed to the lowering oxygen content in samples. Since YBCO is granular in nature, AC susceptibility is used as an effective tool to characterize granular of this system. The inter-granular vortex was investigated with different applied field, Hac, 0.005 – 3.0 Oe at fixed frequency 123 Hz. The matrix critical current density, Jcm was calculated in the framework of Bean’s critical state model. Flux creep activation energy is determined in vortex dynamics exhibited by frequency dependence of AC susceptibility in the range of 123 – 6000 Hz. Sample with x = 0.6 wt% Nd2O3 shows maximum value of Jcm, 5.77 x 10-5 A/cm2 and Ea, 9.212 x 10-19 J indicating at this point it has a optimum pinning centre. As a conclusion, Nd2O3 nanoparticles acting as flux pinning centres in matrixes of superconductors Y123 which gave the best result in term of Jcm value as compared to Gd2O3 and Sm2O3.